2016
DOI: 10.1080/19420862.2016.1171432
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous blockade of VEGF and Dll4 by HD105, a bispecific antibody, inhibits tumor progression and angiogenesis

Abstract: Several angiogenesis inhibitors targeting the vascular endothelial growth factor (VEGF) signaling pathway have been approved for cancer treatment. However, VEGF inhibitors alone were shown to promote tumor invasion and metastasis by increasing intratumoral hypoxia in some preclinical and clinical studies. Emerging reports suggest that Delta-like ligand 4 (Dll4) is a promising target of angiogenesis inhibition to augment the effects of VEGF inhibitors. To evaluate the effects of simultaneous blockade against VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
1
32
0
1
Order By: Relevance
“…We found that ABT-165 was well tolerated in monkeys even at doses as high as 200 mg/kg, with nonadverse histopathologic findings noted only in the liver and thymus. Of note, DLL4 inhibition alone is known to induce endothelial cell proliferation that could be VEGF-dependent (6,39). Therefore, we hypothesized that dual DLL4 and VEGF inhibition may mitigate some normal tissue toxicity derived from DLL4 inhibition alone by potentially restoring the balance of DLL4 and VEGF pathways thereby, preventing proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that ABT-165 was well tolerated in monkeys even at doses as high as 200 mg/kg, with nonadverse histopathologic findings noted only in the liver and thymus. Of note, DLL4 inhibition alone is known to induce endothelial cell proliferation that could be VEGF-dependent (6,39). Therefore, we hypothesized that dual DLL4 and VEGF inhibition may mitigate some normal tissue toxicity derived from DLL4 inhibition alone by potentially restoring the balance of DLL4 and VEGF pathways thereby, preventing proliferation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…A bispecific approach represents an attractive combination strategy to efficiently inhibit both targets, and currently two other DLL4/VEGF bispecific biologics in addition to ABT-165 have been recently reported, HD105 (39) and OMP-305B83 (40). HD105 was engineered by fusing a DLL4-targeting single-chain variable fragment (scFv) to the C-terminal of an anti-VEGF mAb.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to single-target antibody fragment, there is also multiple-target antibody fragment for the treatment of tumours. Recently, bispecific antibodies HD105 that inhibit angiogenesis by targeting vascular endothelial growth factor (VEGF) and Delta-like ligand 4 (DII4) are constructed [78]. Both target sites promote tumour angiogenesis in a variety of tumours, and DII4 is also associated with cancer stem cells.…”
Section: Intrinsic Therapeutic Effect Of Antibody Fragmentsmentioning
confidence: 99%
“…The tumor-suppressive effects are more prominent when both VEGF and DLL4 agents are used in combination [15][16][17]. HD105, a novel antibody designed to target both VEGF and DLL4, is formed by an anti-VEGF antibody linked with anti-DLL4 single-chain Fv [18].…”
Section: Introductionmentioning
confidence: 99%